2017
DOI: 10.3389/fphys.2017.00552
|View full text |Cite|
|
Sign up to set email alerts
|

Reviewing the Role of the Efferent Vestibular System in Motor and Vestibular Circuits

Abstract: Efferent circuits within the nervous system carry nerve impulses from the central nervous system to sensory end organs. Vestibular efferents originate in the brainstem and terminate on hair cells and primary afferent fibers in the semicircular canals and otolith organs within the inner ear. The function of this efferent vestibular system (EVS) in vestibular and motor coordination though, has proven difficult to determine, and remains under debate. We consider current literature that implicate corollary dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 166 publications
(280 reference statements)
1
26
0
Order By: Relevance
“…It has been shown that cochlear efferents have to be stimulated at least at 10 Hz to facilitate their normally low probability of release (Ballestero et al, 2011), and it is a reasonable assumption that the same is required for vestibular efferents. Vestibular efferents in mouse brainstem slices (Leijon and Magnusson, 2014;Mathews et al, 2015Mathews et al, , 2017 have spontaneous resting discharges of up to 5 spikes/s. The main input to efferent neurons is provided by the vestibular nuclei, and the spontaneous activity of vestibular nuclei neurons is ϳ5 times higher in alert mice (57.5 Ϯ 4.2 spike/s) (Beraneck and Cullen, 2007) compared Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cochlear efferents have to be stimulated at least at 10 Hz to facilitate their normally low probability of release (Ballestero et al, 2011), and it is a reasonable assumption that the same is required for vestibular efferents. Vestibular efferents in mouse brainstem slices (Leijon and Magnusson, 2014;Mathews et al, 2015Mathews et al, , 2017 have spontaneous resting discharges of up to 5 spikes/s. The main input to efferent neurons is provided by the vestibular nuclei, and the spontaneous activity of vestibular nuclei neurons is ϳ5 times higher in alert mice (57.5 Ϯ 4.2 spike/s) (Beraneck and Cullen, 2007) compared Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence for α9 * nAChRs/SK in bird and mammalian crista hair cells (Li and Correia, 2011 ; Zhou et al, 2013 ; Yu et al, 2014 ; Poppi et al, 2015 ), but the relationship among hair cell location, α9 * nAChRs expression and corresponding efferent-mediated afferent responses in these species has not been resolved (Dickman and Correia, 1993 ; Lustig et al, 1999 ; Li and Correia, 2011 ). Furthermore, using efferent-mediated response in vestibular afferents to map out α9 * nAChRs in hair cells is particularly challenging in mammals since afferents are invariably excited by efferent stimulation (Goldberg and Fernández, 1980 ; Marlinski et al, 2004 ; Holt et al, 2015b ; Mathews et al, 2017 ). Our data demonstrate that α9 * nAChR-mediated changes in hair cell currents and voltages vary across the neuroepithelium, being larger in type II hair cells in the torus region than those in the central zone, while no apparent ACh responses were observed in hair cells from the planum region.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular efferent neurons (VENs) branch extensively to produce many presynaptic varicosities abutting hair cells, and both bouton and calyceal afferent processes (Smith and Rasmussen, 1968 ; Sans and Highstein, 1984 ; Lysakowski and Goldberg, 1997 ; Purcell and Perachio, 1997 ; Jordan et al, 2013 ). VENs, upon stimulation, may inhibit and/or excite the background discharge of vestibular afferents by activating acetylcholine receptors (AChRs) at each of these synaptic contacts (Goldberg and Fernández, 1980 ; Rossi et al, 1980 ; Highstein and Baker, 1985 ; Brichta and Goldberg, 2000b ; Boyle et al, 2009 ; Mathews et al, 2017 ). Pharmacological data indicate that the subsequent activation of both nicotinic (nAChRs) and muscarinic ACh receptors (mAChRs) on hair cells and afferents underlie many of these efferent-mediated inhibitory and excitatory responses (Guth et al, 1998 ; Holt et al, 2011 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the proposed algorithm is also able to generate nerve fiber orientation fields for various nerve volume shapes present in the vestibular model (like the IAC). It should also be noted that no fibers of the vestibular efferent system were considered in our model, since its distinct functional role in motor and vestibular coordination is not clear yet and varies significantly between species (Marianelli et al, 2015 ; Mathews et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%